Exercise training reduces ventricular arrhythmias through restoring calcium handling and sympathetic tone in myocardial infarction mice. Issue 4 (25th February 2019) - Qin, Rujie; Murakoshi, Nobuyuki; Xu, DongZhu; Tajiri, Kazuko; Feng, Duo; Stujanna, Endin N.; Yonebayashi, Saori; Nakagawa, Yoshimi; Shimano, Hitoshi; Nogami, Akihiko; Koike, Akira; Aonuma, Kazutaka; et al.
Abstract: Exercise can improve morbidity and mortality in heart failure patients; however, the underlying mechanisms remain to be fully investigated. Thus, we investigated the effects of exercise on cardiac function and ventricular arrhythmias in myocardial infarction (MI) induced heart failure mice. Wild‐type male mice underwent sham‐operation or permanent left coronary artery ligation to induce MI. MI mice were divided into a sedentary (MI‐Sed) and two intervention groups: MI‐Ex (underwent 6‐week treadmill exercise training) and MI‐βb (oral bisoprolol treatment (1 mg/kg/d) without exercise). Cardiac function and structure were assessed by echocardiography and histology. Exercise capacity and cardiopulmonary function was accepted as oxygen consumption at peak exercise (peak VO2 ). Autonomic nervous system function and the incidence of spontaneous ventricular arrhythmia were evaluated via telemetry recording. mRNA and protein expressions in the left ventricle (LV) were investigated by real‐time PCR and Western blotting. There were no differences in survival rate, MI size, cardiac function and structure, while exercise training improved peak VO2 . Compared with MI‐Sed, MI‐Ex, and MI‐βb showed decreased sympathetic tone and lower incidence of spontaneous ventricular arrhythmia. By Western blot, the hyperphosphorylation of CaMKII and RyR2 were restored by exercise and β‐blocker treatment. Furthermore, elevated expression of miR‐1 and decreased expression of its target protein PP2A were recovered by exercise and β‐blocker treatment. Continuous intensive exercise training can suppress ventricular arrhythmias in subacute to chronic phase of MI through restoring autonomic imbalance and impaired calcium handling, similarly to that for β‐blockers. Abstract : The benefits of exercise on heart failure after myocardial infarction (MI) have been well established, while the underlying mechanisms remain to be fully investigated. Our study showed that continuous intensive exercise training can suppress ventricular arrhythmias in subacute to chronic phase of MI through restoring autonomic imbalance and impaired calcium handling, similarly to that for β‐blockers. In addition, we suggested a novel possible mechanism that the antiarrhythmic effects of exercise or β‐blocker treatment are, at least in part, attributed to regulations of miR‐1‐mediated PP2A activity and its downstream targets, hyperphosphorylated CaMKII‐RyR2, in MI.